NEEDLE STICK AND SHARPS INJURIES AND ITS RISK FACTORS AMONG HEALTH CENTER PERSONNEL (ASTARA IRAN, 2006) - R Lotfi, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Blood borne diseases are still one of the major sources of nosocomial infections and are large concern of health personnel because of extension of HIV infection. The aim of this study was to determine the occurrence and risk factors of needle stick and sharps injuries among personnel of hospitals and health centers in Astara, Iran.METHODS: In this cross sectional study, a total of 90 nurses, midwives, physicians, laboratory technicians, operation technicians, nurse aids, and anesthesia personnel, involve in the direct management and care of patients answered a questionnaire that had questions about occurrence of needle stick and sharps injuries and some potential risk factors.FINDINGS: The rate of needle stick injury was 1.9 per person in a year. A 67% of personnel had at least one needle stick injury in the last year. Only 20% of these hadn’t any injury from needle stick duration entire work career. Multiple logistic regression analysis showed that the most important risk factor for needle stick injuries was working night shifts, (OR: 2.5, 95% CI 1.5-4.8). Other important risk factor including lack of training on such injuries (OR: 1.89, 95% CI 1.1-3.4), number of patients attended daily or nightly (OR: 1.81, 95% CI 1.1-2.8) and recapping needles (OR: 1.67, 95% CI 1.1-2.3).CONCLUSION: The rate of needle stick injury is fairly high among health care personnel of Astara and is a cause of the spread of blood borne diseases including HIV, hepatitis B, hepatitis C and the most important risk factor was the number of night shifts and lack of training. So training program especially for personnel who work the night shift is recommended to prevent needle stick injury.